ASSESSMENT OF THE IMPACT OF URBANIZATION GROWTH ON THE CLIMATE OF BAGHDAD PROVINCE USING REMOTE SENSING TECHNIQUES. - Mahal, Sarmad.H.; Al-Lami , A. M.; Mashee, F. K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to recognize the spatial and temporal features of urban development and its impact on the climate of Baghdad City. The analytical method of the study relies on changes in Land Use/Land Cover (LULC), Normalized Difference Vegetation Index (NDVI), Normalized Difference Built-up Index (NDBI), and Land Surface Temperature(LST); GIS technology was used to measure these statistics. Landsat (5,8) and Sentinel2A imagery were used to detect the change of urbanization growth, vegetation change, and land surface temperature during the study period from 2001 to 2020, whereas used the supervised classification technique for determination for LULC variations. The results showed significant changes among the LULC classes in the studied periods, as most of the LULC changes were caused by human activities. The most prominent changes in LULC were the urban expansion on agricultural land, continuously in all years, which led to the decline of vegetation resulting from land degradation. The Building area increased from around 863 km2 in 2001 to 1469 km2 in 2020 concentrated mainly in the center, the northeastern and southeastern part of the city. Moderate plants decrease from around 88.5 km2 in 2001 to 59 km2 in 2020 and dense plants decreased from 0.0252 km2 in 2001 to 0.0135 km2 in 2020. This has led to negative effects on the climate where temperature rates increased from (26-47) degrees Celsius in 2001 to (32-56) degrees Celsius in the last year of the study, the highest temperatures were recorded in urban growth areas and areas without vegetation.